2022
DOI: 10.3390/ijerph19042066
|View full text |Cite
|
Sign up to set email alerts
|

Selected Elements of Lifestyle and the Level of Functional Fitness in Older Women

Abstract: Background: The appropriate level of functional fitness is a very important element for seniors to maintain self-reliance in daily life. The aim of this research was to assess sociodemographic differences, selected elements of lifestyle, and functional fitness in the older residents of social welfare homes and community dwellers Methods: The analysed group comprised 693 women aged 65–79, including 173 subjects living in social welfare homes and 520 community-dwelling women. Basic anthropometric features were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Scores on all attempts of the test were found to be significantly lower in the group of female SWH residents compared to seniors living in the community. The weakest attempts in the SWH group were 8-foot up and go and 30-second chair, in which, respectively, 87.3% and 74.6% of the seniors tested did not reach the norms developed for the Polish population [ 40 ]. In another Polish study of the functional fitness of older women from SWH, the weakest tests were 8-foot up and go and 6-minute walk, in which only a few percent of the seniors tested met Polish norms [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scores on all attempts of the test were found to be significantly lower in the group of female SWH residents compared to seniors living in the community. The weakest attempts in the SWH group were 8-foot up and go and 30-second chair, in which, respectively, 87.3% and 74.6% of the seniors tested did not reach the norms developed for the Polish population [ 40 ]. In another Polish study of the functional fitness of older women from SWH, the weakest tests were 8-foot up and go and 6-minute walk, in which only a few percent of the seniors tested met Polish norms [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order for seniors in institutions to have a good quality of life and a long life, continuous monitoring of their physical condition and health status is essential. There is a lot of current research on the functional fitness and health status of older people living in the community [ 22 , 24 , 32 35 ] but much less research on institutionalized older people [ 36 39 ] and especially in Poland [ 16 , 40 , 41 ]. Furthermore, the associations of physical fitness with physical activity and health status among seniors living in social welfare homes and in the community have been poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown similar results [ 27 ]. Therefore, an appropriate level of physical fitness is an important element for older people to maintain their autonomy [ 28 ]. However, these studies did not examine this topic considering the levels of physical activity practiced in the same way as the present study has done.…”
Section: Discussionmentioning
confidence: 99%